1999
DOI: 10.1002/chin.199950017
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Characterization of V2O5—TiO2 Catalysts by Milling by ESR and Solid State 1H and 51V NMR.

Abstract: 1999 magnetic resonance, nuclear quadrupole resonance magnetic resonance, nuclear quadrupole resonance (solids and liquids) D 6560 50 -017 Characterization of V 2 O 5 -TiO 2 Catalysts by Milling by ESR and Solid State 1 H and 51 V NMR. -Milling of V 2 O 5 /TiO 2 mixtures induces spreading of vanadia across the titania surface, whereby two types of V 5+ species strongly bonded to titania are formed. In addition, V 3+ centers and at least three structurally different V 4+ centers are detected. -(LAPINA, OLGA B.;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(26 citation statements)
references
References 1 publication
1
25
0
Order By: Relevance
“…The fitting of 27 Al MAS NMR spectra was carried out using Dmfit software 42 by implementation of Czjzek model (SzSimple) for simulation of quadrupole constant distribution. The 27 Al MAS NMR spectra have obviously no perfect quadrupole peak shape of crystalline materials; 43 thus, a correct Table 2. Relative Peak Ratio Obtained from the Decomposition of 15 kHz 29 Si MAS NMR Spectra in Figure 2 relative intensity (a.u.)…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 3 more Smart Citations
“…The fitting of 27 Al MAS NMR spectra was carried out using Dmfit software 42 by implementation of Czjzek model (SzSimple) for simulation of quadrupole constant distribution. The 27 Al MAS NMR spectra have obviously no perfect quadrupole peak shape of crystalline materials; 43 thus, a correct Table 2. Relative Peak Ratio Obtained from the Decomposition of 15 kHz 29 Si MAS NMR Spectra in Figure 2 relative intensity (a.u.)…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The surface OH group investigation by solid-state 1 H MAS NMR is widely applied for many materials, such as alumina, 13,14 silica, 15 aerogels, 16 zeolites, 17−21 titania, 22,23 heteropolyacids, 24 fiberglasses, 25,26 and vanadia. 27 The main drawback of 1 H NMR for surface OH groups is a sophisticated sample treatment prior to the experiment. Generally, the pretreatment requires high temperature dehydration under primary vacuum for several hours (4−12 h).…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, it has been predicted that high levels of hydration can stimulate the leaching of OV(OH) 3 species. 46 Although previously proposed, 53 this study represents the first time that a fraction of vanadia species was distinctly observed as a dissolved vanadia species on the titania surface under hydrated conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 56%